Reaction of submicron aluminum powders with liquid water. Macrokinetics, products, self-heating; Kinetics and Catalysis; Vol. 31, № 4 - Lyashko A. P.; Medvinskii A. A.; Savel'ev G. G.; Ilyin A. P. Aleksandr Petrovich; Yavorovsky N. A. Nikolay Aleksandrovich (1991, 1991)
Oxidation by liquid water of submicron aluminum powders (SMP) prepared by the method of electric explosion of conductors with subsequent passivation was investigated. In contrast to more coarsely disperse powders, SMP undergo high degrees of conversion, up to ? ? 1. An x-ray-amorphous oxide with a specific surface area of up to 500 m2/g is the basic solid product of oxidation of SMP. It is hypothesized that the features of oxidation of SMP are due to self-heating of the particles and their aggregates during the reaction.